Network science and sustainable performance of family businesses in tourism. Issue 2 (10th November 2020) - Baggio, Rodolfo; Valeri, Marco
Abstract : Purpose: There is a little appreciation for the role network science can play in sustainable tourism, and it is not quite clear to what extent generic models from the tourism network analysis literature are applicable. In the international management literature, then, few significant studies exist that deal with the effects of network structures on the sustainable performance of tourism family businesses. This research analyzes these issues and discusses the state of the art of this area. Design/methodology/approach: Based on a scrutiny of the literature conducted on research papers published in the last twenty years, this analysis focuses on the relation between network analysis methods and sustainable performance within the tourism family business domain. The paper uses a limited set of keywords, restricting the selection to tourism and hospitality works on sustainability. A qualitative content analysis is performed. Findings: The results suggest a critical reflection on how the methods of network science can be profitably and advantageously used for supporting a sustainable performance of family businesses in tourism. Originality/value: The paper contains a critical consideration on the potential drivers and drawbacks of the relationship between sustainability and networking in tourism and highlights some managerial implications. The analysis closes with some suggestions and indications for future research work.